2018
DOI: 10.1186/s12877-018-0934-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of conducting research in long-term care facilities: a systematic review

Abstract: BackgroundThe aim of this review is to describe the challenges and barriers to conducting research in long-term care facilities.MethodsA literature search was conducted in Ovid MEDLINE, Embase, Cochrane Central, PsycINFO and CINAHL. Keywords used included “long term care”, “nursing home”, “research”, “trial”, “challenge” and “barrier”, etc. Resulting references were screened in order to identify relevant studies that reported on challenges derived from first-hand experience of empirical research studies. Chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 74 publications
6
78
0
Order By: Relevance
“…Only a minority of the 10,933 of relevant care homes across England were able to be approached. However, although staff from only 74 homes took part, to our knowledge, the 400 respondents is a high response rate for this population in the time available for recruitment (25). Eight further paper copies were also returned but these were incomplete and were not included within the data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Only a minority of the 10,933 of relevant care homes across England were able to be approached. However, although staff from only 74 homes took part, to our knowledge, the 400 respondents is a high response rate for this population in the time available for recruitment (25). Eight further paper copies were also returned but these were incomplete and were not included within the data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The challenges identified in research mirrored those outlined by Lam and colleagues. In their meta-analysis regarding research in LTCF, they identified eight themes that included facility/owner/ administrator factors, resident factors, staff caregiver factors, family caregiver factors, investigator factors, ethical/legal factors, methodological factors and budgetary factors [5]. Our work provided additional depth to their findings by providing a specific context for LTCF research.…”
Section: Discussionmentioning
confidence: 96%
“…Despite concordance being strongest in RACFs, many RACF residents who stated they had not completed ACP documentation actually did have documentation present in their file. Considering most residents in aged care have some degree of cognitive impairment, 43,44 it is possible that some a Self-report frequencies may differ from those reported in Tables 2 and 3 because participants may have had more than one type of ACP document.…”
Section: Discussionmentioning
confidence: 99%